2017
DOI: 10.20897/ejsteme/81285
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of the Graphic Representations of Science Textbooks

Abstract: Textbooks are primary teaching aids, sources from which students obtain knowledge of science domain. Due to this fact, curriculum developers in the field emphasize the crucial role of analysing the contents of science textbooks in improving science education. Scientific domain knowledge relies on graphical representations for the manifestation of itself. Content analysis of the representations therefore entails the necessity of the systematic reading and categorizing of a body of visual representations, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…This finding means that the topics in the middle school science textbooks are mainly taught by concrete images. Iconic representations are effective for students to know the structures and visual appearances of the concepts which can be seen by a naked eye (Khine & Liu, 2017). They can be also used to attract students' attention (Harrison & Treagust, 2003) for teaching a new concept (Johnstone, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding means that the topics in the middle school science textbooks are mainly taught by concrete images. Iconic representations are effective for students to know the structures and visual appearances of the concepts which can be seen by a naked eye (Khine & Liu, 2017). They can be also used to attract students' attention (Harrison & Treagust, 2003) for teaching a new concept (Johnstone, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The representations in the middle school science textbooks were analyzed concerning the combination of two main diagram coding schemes. The first one was developed by Khine and Liu (2017) according to the Graphical Analysis Protocol designed by Slough, McTigue, Kim, and Jennings (2010). Four categories from the scheme, which are graphical types, gender, indexing and captioning involved in the scheme used for the current research.…”
Section: Instrumentsmentioning
confidence: 99%
“…In this way, the use of a mixed diagram of visual representation and written text is the most common method used in modern science textbooks. In other words, science textbooks include strategies that help learners understand key science concepts through diagrams (Khine & Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prior researches have been conducted on textbooks in the United Arab Emirates (UAE; Abosalem, 2016;Al-Qatawneh et al, 2019;Khine & Yang, 2017). However, most of these studies reported different issues related to school textbooks and not to the textbooks used by higher education institutions.…”
Section: Introductionmentioning
confidence: 99%